Digitale Exploration und hermeneutische Bewertung: Profilierung einer frühneuzeitlichen Gelehrtenfigur mittels Netzwerkanalyse am Beispiel von Leonhard Christoph Sturm (1669–1719) - Maximilian Görmar; Jörn Münkner; Hartmut Beyer (Zeitschrift für digitale Geisteswissenschaften, 2022)
The early modern republic of letters has largely been analysed as an epistolary network. In this case study on Leonhard Christoph Sturm (1669–1719) we suggest a broader approach which integrates data on letters and publications from the VD 17, VD 18, and Kalliope catalogues along with a reconstruction of Sturm’s library. Based on this data we perform an exploratory network analysis which, in turn, informs a hermeneutic inquiry in two key areas of Sturm‘s scholarly interest: the design of fortifications and theology. In this way, we offer a comprehensive methodology which combines distant and close reading to study the intellectual networks of the early Enlightenment around 1700.